Designing a Complex System of Coffee Shop by Using Cognitive Work Analysis to Evaluate the Operations - Hastawati Chrisna Suroso; Saruda Jirakulthana (Journal of Research and Technology, 2023)
The development of coffee shop is increasing whether in Europe or Asia. The system in coffee shop are need to be improved as the human mobile are getting higher and people has no more time in waiting. The demand of consumer about coffee shop system is getting wider so that a system in it are need to be discuss. Cognitive Work Analysis (CWA) is expected to outline parts in the system so that it can be extracted to analyze and evaluate the existing system. This tools is a method to analyze industrial complex system which is useful for industrial design. CWA are extracted into five phase which has different aims in each phase. The result of this research are produces seven function and five situation in control task analysis. In collecting the data, this research use brainstorming as qualitative method and found out four categories in WDA, seven categories in CTA, nine categories in WCA. The coffee shop system are need to be improved as the human mobile are getting higher and people has no more time in waiting. The customer demand about coffee shop system is getting vary so that an improvement are need to be discuss. Cognitive Work Analysis is expected to outline parts in the system so that it can be extracted to analyze and evaluate the existing system. This tools is a method to analyze industrial complex system which is useful for industrial design. The result of this research are produces seven function and five situation in control task analysis